The relationship between workplace bullying and professional self‐concept in Iranian nurses - Amin Hosseini; Seyed Hossein Mousavi; Fatemeh Hajibabaee; Shima Haghani (Wiley, 2021)
Abstract Aim To determine the level of workplace bullying among Iranian nurses and its relationship with their professional self‐concept. Design This was a descriptive correlational study. Methods This study was performed on 200 nurses working in the emergency departments and intensive care units of Imam Khomeini Hospital Complex affiliated to Tehran University of Medical Sciences, Iran, in 2020. The participants were chosen using the simple random sampling method and data collection tools were Negative Acts Questionnaire-Revised and Nurse Self‐Concept Questionnaire. The Pearson correlation coefficient was used to determine the relationship between workplace bullying and professional self‐concept. Results Based on the experience of daily or weekly workplace bullying, the mean scores of workplace bullying in nurses in terms of work‐related bullying, person‐related dimension and physical intimidation were 10.11%, 4.27% and 5.66%, respectively, and the overall mean score was 6.68%. The results of this study also showed that workplace bullying is inversely related to professional self‐concept and almost all of its dimensions (p = .002, r = −.219).